The Effect Of Giving Edamame Beans On Breast Milk Production In Post Partum Mothers At The Tanjung Midwife Clinic In East Kisaran City District - Kardina Hayati; Tati Murni Karo Karo; Rahmad Gurusinga; Widya .; Latifatul Robbaniyah (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2021)
During breastfeeding, mothers are recommended to increase their intake of energy, protein, calcium, iron, folic acid, and other vitamins and minerals to meet the nutritional needs of breastfeeding. In order for mothers to produce 1 liter of breast milk, additional food is needed. Edamame plant is a local food ingredient that has potential for nutrition for nursing mothers, because it contains phytosterol compounds that function to increase and facilitate breast milk production (lactagogum effect). This study aims to see whether there is an effect of giving edamame nuts to breast milk production in postpartum mothers at the Midwife Clinic Putri Tanjung, Kota Kisaran Timur District in 2021. This type of research is a Quasy Experiment Design using the one Group Pretest-Postest Design, with a total sample of 8 person. Data collection uses primary data and secondary data. The data analysis technique is using the Wilcoxon test. Based on the Wilcoxon test, the results showed that post-partum mothers gave edamame nuts pre-test and post-test with a sample of 8 respondents having a P-value (0.008) < 0.05 then H0 was rejected. test and post-test on the administration of edamame nuts on breast milk production in postpartum mothers at the Tanjung Putri Midwife Clinic, East Kisaran City District in 2021. It is recommended for health workers to provide information about giving edamame nuts as an alternative to increase breast milk production for postpartum mothers.